IMPLIKASI ALIRAN FILSAFAT PENDIDIKAN DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM - Ifana Nafiatussania (PT. Intelek Cendikiawan Nusantara, 2024)
Islamic education aims to shape holistic individuals (insan kamil) who integrate faith, knowledge, and virtuous deeds. In developing Islamic education curricula, educational philosophy serves as a vital foundation, providing a framework to understand the nature of humanity, educational goals, and ideal teaching methods. This article analyzes the implications of educational philosophical schools, such as idealism, realism, pragmatism, and existentialism, on the development of Islamic education curricula. Each philosophy offers unique contributions: idealism emphasizes character and spirituality development, realism promotes the integration of worldly and spiritual knowledge, pragmatism ensures the relevance of education to modern needs, and existentialism helps learners find life’s purpose within the framework of tawhid (monotheism). This study employs a qualitative approach with descriptive analysis through literature reviews. The findings reveal that integrating these four philosophical schools can create a holistic, relevant curriculum grounded in Islamic values. However, the primary challenge lies in balancing spiritual, intellectual, and practical aspects without compromising Islamic identity. This research provides recommendations for developing adaptive, project-based curricula that encourage self-reflection to nurture intellectually competent, faithful individuals capable of addressing global challenges.